An exploration of alginate oligosaccharides modulating intestinal inflammatory networks via gut microbiota - Zhang, Zhikai; Wang, Xuejiang; Li, Feng (Frontiers in Microbiology, 2023)
Alginate oligosaccharides (AOS) can be obtained by acidolysis and enzymatic hydrolysis. The products obtained by different methods have different structures and physiological functions. AOS have received increasing interest because of their many health-promoting properties. AOS have been reported to exert protective roles for intestinal homeostasis by modulating gut microbiota, which is closely associated with intestinal inflammation, gut barrier strength, bacterial infection, tissue injury, and biological activities. However, the roles of AOS in intestinal inflammation network remain not well understood. A review of published reports may help us to establish the linkage that AOS may improve intestinal inflammation network by affecting T helper type 1 (Th1) Th2, Th9, Th17, Th22 and regulatory T (Treg) cells, and their secreted cytokines (the hub genes of protein-protein interaction networks include interleukin-1 beta (IL-1β), IL-2, IL-4, IL-6, IL-10 and tumor necrosis factor alpha (TNF-α)) via the regulation of probiotics. The potential functional roles of molecular mechanisms are explored in this study. However, the exact mechanism for the direct interaction between AOS and probiotics or pathogenic bacteria is not yet fully understood. AOS receptors may be located on the plasma membrane of gut microbiota and will be a key solution to address such an important issue. The present paper provides a better understanding of the protecting functions of AOS on intestinal inflammation and immunity.